On the Global Dynamics of a Fourth-Order Riccati-Type Exponential Fuzzy Difference Equation - Asifa Tassaddiq; Muhammad Tanveer; Muhammad Usman; Dalal Khalid Almutairi; Rabab Alharabi (Axioms, 2025)
Fuzzy systems play a crucial role in emerging fields such as artificial intelligence, machine learning, and computer science, drawing significant research interest in fuzzy difference equations. Inspired by this, we analyze the dynamic properties of a fourth-order exponential Riccati-type fuzzy difference equation. The study is further extended to a system of fourth-order fuzzy difference equations. We investigate the boundedness, as well as the local and global stability, of positive solutions. To support the theoretical findings, numerical examples are presented along with graphical and tabular representations.